Pengaruh Ekstrak Biji Pepaya (Carica papaya, L.) Pada Tahap Prakopulasi Terhadap Fungsi Reproduksi Mencit (Mus musculus, L.) Swiss Webster Betina - Siburian, Jodion; Marlina, Jeri; Johari, Asni (Biospecies, 2008)
The aim of this experiment was to study the effect of Carica papaya Linn seeds extract on pracopulation onthe reproductive function of swiss Webster female mice (Mus musculus L.). Parametric are: body weight, thenumber implantation, number live fetuses, number death fetuses and embryionic fetuses, post-implantationdeath, live fetuses were examined, libido and ovarium weight. The experiment was designed using thecomplete randomized design. The results tested using the DNMRT method. Treatment are control withoutCarboksil Metil Celulose (CMC) 1% (K0), control with CMC 1% (KCMC), Carica papaya ekstrac dosage 50, 75and 100 mg/kgbb (E50, E75 and E100). The results experiment showed that Carica papaya L. ekstrac candestroyed could disturbed the reproduction function, i.e disturbed accreation body weight for gestation, bodyweight mice 18 th day of gestation, decrease the number live fetuses, increase number death fetuses andpost-implantation death, there number embryonic resorption and body weight live fetuses treatment morelower concentrated control. But, no influence significant for number implantation and ovarium weight.